Power of the Shamans in Village Governance Systems Benteng Kota as a Corruption Prevention Strategy - Kodri, M. Adha Al (International Journal of Psychosocial Rehabilitation, 2020)
Due to corruption remains a major enemy in Indonesia, this study is to analyze the potential of local wisdom in Bangka Belitung Islands, as a strategy to eradicate corruption which one of them using power of the shamans in the governance system as in Benteng Kota village. This research used ethnography approach. The study showed the fact that legitimacy and belief system of the society that gave birth a social authority as it could be a strong social capital to be exploited by the government as one of the strategies in the prevention of corruption. The results concluded that one of the strategy to prevent corruption can be done through the local wisdom appoach, namely through the presence of shamans as a controller that serves to suppress the intent and opportunity of apparatus to conduct corruption. Researchers recommend that this local wisdom can become a model of eradication that starts from the village. Since the presence of shamans power can create a more transparent village government and a policy that is really favoring to the interests of people in a society.